A Comparison of In vitro Mass Propagation of Kew with Mauritius Type of Pineapple (Ananas comosus Merr L.) - Gamage, N.; Laksiri, B.D.P.; Hirimburegama, Kshanika (My University, 1995)
Ananas comosus L. Merr (Pineapple) is conventionally propagated through suckers, slips and ratoons taken from existing cultivations. These planting materials are not homogeneous and this is a major difficulty that farmers face in large scale cultivations. In vitro micropropagated plants offer a possible answer due to their high level of uniformity. As propagation of Mauritius type, through in vitro meristem culture is already established, a similar technique for mass propagation of Kew type (Smooth Cayenne) was compared in this study. Shoots were proliferated on Murashige and Skoog (1962) liquid and semi-solid media, supplemented with benzyl amino purine (BAP, 2.5 \imol) and indole acetic acid (IAA, 1.25 pmol). A higher proliferation was detected in liquid than in semi-solid media, but was less than that of Mauritius type. Plants were successfully regenerated on BAP (1.25 \imol) and IAA (1.25 fimol) semi-solid media. Similar results were observed on Agar (BDH) and unpurified moss jelly as the solidifying agent, suggesting that agar could be replaced with less expensive moss jelly. Plants rooted on MS with indole butyric acid (IBA, 1.25 fimol) resumed independent growth after eight weeks of acclimatization in the green house